Method for correcting compressive strength of large-particle-size cement stabilized macadam non-standard test piece
By constructing and calibrating the three -dimensional discrete element numerical model of large -scale cement stabilization gravel test parts, the relationship between stress resistance and test parts is established, and the problem of inconsistent pressure of different sizes of test parts is solved, and large -particle size cement is achieved. Accurate assessment of stable gravel material pressure resistance.
Patent Information
- Application Number
- CN202411441146.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Due to the uneven distribution of aggregates inside test pieces of different sizes and random distribution of meticulous defects such as gap cracks, the compressive strength measurement of large-particle cement stable gravel materials in indoor tests is inconsistent, which affects the reliability of the test results.
By determining the resistance value of the benchmark test piece, build a three -dimensional discrete element numerical model of the test parts, and use the resistance value of the benchmark test parts to calibrate the model to simulate the compressive strength value, establish the destructive strength and the size of the test parts size The intensity volume expression is determined to determine the compressive strength correction coefficient, and then obtain the real compressive strength value of the large -scale cement stabilized gravel test parts.
This method can accurately evaluate the pressure resistance of large -scale large -scale cement stabilization gravel test parts, improve the reliability of the test results, and be suitable for the compression strength of the large -particle -size cement stabilized gravel layer in the field of road engineering.
Smart Images

Figure CN119378068A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering, and in particular to a method for correcting the compressive strength of a non-standard test piece of large-diameter cement-stabilized crushed stone. Background Art
[0002] Traditional cement-stabilized crushed stone base is greatly affected by temperature and humidity, and is prone to shrinkage cracks. Under the action of traffic load, the cracks gradually expand upward to form reflective cracks, which seriously affect the service life of asphalt pavement. Large-size cement-stabilized crushed stone is composed of large-size main aggregates to form a framework, and cement-stabilized crushed stone fillers to fill the gaps. The strength mainly comes from the skeleton intercalation of large-size crushed stone. In addition, large-size crushed stone has a small specific surface area, and the amount of cement required to wrap the aggregate is small. The use of large-size cement-stabilized crushed stone base can effectively prevent the occurrence of reflective cracks in asphalt pavement.
[0003] In the composition design of large-size cement-stabilized crushed stone materials, compressive strength is a key control indicator. Due to the uneven distribution of aggregates in specimens of different sizes and the random distribution of microscopic defects such as voids and cracks, the compressive strength of specimens of different sizes measured in indoor tests is inconsistent, affecting the reliability of the test results. Therefore, only by fully understanding the variation of the compressive strength of large-size cement-stabilized crushed stone with the size of the specimen can the mechanical properties of the mixture be better guaranteed.
[0004] At present, domestic research on the use of large-size cement-stabilized gravel materials for road bases mainly focuses on the mechanical properties and durability of large-size cement-stabilized gravel. The "Technical Specifications for the Construction of Filled Large-size Cement-stabilized Gravel Bases" (T / CECS G:K23-01-2019) stipulates that large-size gravel is a single-specification aggregate with a maximum nominal particle size of 73mm. The specification does not specify the size of the compressive strength test piece of the mixture. Normally, the size of the test mold should be more than 4 times the maximum particle size of the aggregate. Considering the difficulty of self-made molds and test operations, most researchers have formed There are certain limitations in testing the compressive strength of large-size cement-stabilized crushed stone with cylindrical specimens, or only conducting experimental research on fillers in large-size cement-stabilized crushed stone. Some scholars have considered the specimen size issue and set a specimen size in the experimental research, but whether the self-determined specimen size is reasonable and whether the measured data is valid still needs further verification. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone. The present invention solves the problem in the prior art of inaccurate test results caused by inconsistent compressive strength under specimens of different sizes.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] A method for compressive strength correction of non-standard specimens of large-size cement-stabilized crushed stone, comprising:
[0008] Determining a reference specimen and performing a compressive strength test on the reference specimen to obtain a compressive strength value of the reference specimen;
[0009] Constructing a three-dimensional discrete element numerical model of the specimen and calibrating the three-dimensional discrete element numerical model of the specimen using the compressive strength value of the reference specimen to obtain a calibrated three-dimensional discrete element numerical model of the specimen;
[0010] Using the calibrated three-dimensional discrete element numerical model of the specimen, numerical simulation of the compressive strength of large-diameter cement-stabilized crushed stone specimens of different sizes is performed to obtain a destructive strength set;
[0011] According to the volumes of the large-size cement-stabilized crushed stone specimens of different sizes, the volumes of the benchmark specimens, the compressive strength values of the benchmark specimens and the destructive strength set, a strength volume expression of destructive strength and specimen size is obtained, wherein the strength volume expression includes: an abscissa expression and a strength ordinate expression;
[0012] Determine the compressive strength correction factor of the large-size cement-stabilized crushed stone specimen using the strength volume expression;
[0013] The true compressive strength value of the large-size cement-stabilized crushed stone specimen is obtained by using the compressive strength correction coefficient and the compressive strength value of the reference specimen.
[0014] Preferably, the reference specimen is a large-diameter cement-stabilized gravel specimen of 200mm×200mm×200mm.
[0015] Preferably, the side surface of the reference specimen is a pressure-bearing surface.
[0016] Preferably, the constructing of the three-dimensional discrete element numerical model of the specimen and calibrating the three-dimensional discrete element numerical model of the specimen using the compressive strength value of the reference specimen to obtain the calibrated three-dimensional discrete element numerical model of the specimen includes:
[0017] Obtaining three-dimensional profile information of aggregate of the benchmark specimen;
[0018] According to the three-dimensional contour information, the large-size crushed stone is uniformly generated step by step from large to small particle sizes using the clump distribute command, and the coarse aggregate in the filling material is generated using the ball distribute command to obtain a three-dimensional discrete element numerical model of the initial specimen;
[0019] The virtual specimen was loaded, the loading speed of the left and right walls was set to 0.05 m / s, and the microscopic parameters were adjusted multiple times to obtain the calibrated three-dimensional discrete element numerical model of the specimen.
[0020] Preferably, the intensity volume expression is:
[0021] y=Aexp(-Bx)+C
[0022]
[0023] Where: R c For any volume V c The compressive strength value of the non-standard (benchmark) specimen (200 mm), R0 is the compressive strength value of the non-standard (benchmark) specimen (200 mm), V0 is the volume of the non-standard (benchmark) specimen, exp is the exponential fitting formula, and A, B and C are the fitting constants respectively.
[0024] Preferably, the expression of the true compressive strength value is:
[0025] R' c =aR0;
[0026] Among them, R' c is the true compressive strength value of the large-size cement-stabilized crushed stone specimen, a is the compressive strength correction coefficient of the large-size cement-stabilized crushed stone non-standard specimen, and R0 is the compressive strength value of the non-standard (benchmark) specimen (200 mm).
[0027] A specimen molding device, comprising:
[0028] Removable test mold and vibratory compactor;
[0029] The detachable test mold is used to load the reference test piece, and the vibration compactor is used to perform vibration compaction on the reference test piece.
[0030] Preferably, the detachable trial mold comprises:
[0031] Base, front and rear baffles, left and right baffles, long bolt rods, short bolts and nuts;
[0032] The front and rear baffles and the left and right baffles are installed at the front, rear, left and right positions of the base. The front and rear baffles are fixedly connected by two groups of long bolt rods and nuts, one group on each side. Each group consists of two long bolt rods and four nuts, and are symmetrically distributed along the central axis of the test mold. There is a protruding short bolt in the middle of the base and it is fixed to the long bolt rod by a nut.
[0033] The present invention discloses the following technical effects:
[0034] The present invention provides a method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized gravel. First, the method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized gravel proposed in this patent is applicable to the determination of the compressive strength of large-size cement-stabilized gravel bases in the field of road engineering, and the method has strong applicability. The test mold structure combination is simple and ingenious, and it is easy to disassemble, avoiding a large number of time-consuming and labor-intensive indoor tests. The simulated data is reliable, and the compressive strength values of large-size cement-stabilized gravel under different maximum nominal particle sizes can be accurately obtained; second, through the method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized gravel proposed in this patent, in indoor tests, non-standard cubic specimens with a specimen size of 200 mm can be directly formed, and the true compressive strength value can be corrected by this method, thereby accurately evaluating the mechanical properties of large-size cement-stabilized gravel mixtures. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0036] Figure 1 A flow chart of a method for correcting the compressive strength of a non-standard specimen of large-size cement-stabilized crushed stone provided in an embodiment of the present invention;
[0037] Figure 2 A schematic diagram of a discrete element model of large-size cement-stabilized crushed stone provided in an embodiment of the present invention;
[0038] Figure 3 A schematic diagram of the relationship between the strength ratio and volume ratio of samples of different sizes provided in an embodiment of the present invention;
[0039] Figure 4 A schematic diagram of a detachable trial mold structure provided in an embodiment of the present invention.
[0040] Description of reference numerals:
[0041] 1-base; 2-front and rear baffles; 3-left and right baffles; 4-long bolt rod; 5-short bolt; 6-nut. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0044] like Figure 1 As shown, the present invention provides a method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone, comprising:
[0045] Step 100: determining a reference specimen and performing a compressive strength test on the reference specimen to obtain a compressive strength value of the reference specimen;
[0046] Specifically, non-standard specimens of large-size cement-stabilized crushed stone were formed as reference specimens, and the compressive strength tests were carried out on the specimens.
[0047] Step 200: constructing a three-dimensional discrete element numerical model of the specimen and calibrating the three-dimensional discrete element numerical model of the specimen using the compressive strength value of the reference specimen to obtain a calibrated three-dimensional discrete element numerical model of the specimen;
[0048] Specifically, with the help of discrete element software PFC3D, a three-dimensional discrete element numerical model of non-standard (benchmark) specimens of large-size cement-stabilized crushed stone was constructed, and the model was calibrated at the mesoscopic level using the compressive strength test results.
[0049] Step 300: using the calibrated specimen three-dimensional discrete element numerical model to perform compressive strength numerical simulation on large-size cement-stabilized crushed stone specimens of different sizes to obtain a destructive strength set;
[0050] Step 400: obtaining a strength volume expression of destructive strength and specimen size according to the volumes of the large-size cement-stabilized crushed stone specimens of different sizes, the volume of the reference specimens, the compressive strength values of the reference specimens and the destructive strength set, wherein the strength volume expression includes: a physical examination abscissa expression and a strength ordinate expression;
[0051] Step 500: Determine the compressive strength correction factor of the large-size cement-stabilized crushed stone specimen using the strength volume expression;
[0052] Step 600: derive the true compressive strength value of the large-size cement-stabilized crushed stone specimen by using the compressive strength correction coefficient and the compressive strength value of the reference specimen.
[0053] Furthermore, the benchmark specimen is a large-size cement-stabilized crushed stone specimen of 200 mm×200 mm×200 mm. The maximum nominal particle size d of the large-size cement-stabilized crushed stone mixture max ≥53mm.
[0054] Specifically, the synthetic gradation of large-size cement-stabilized crushed stone is shown in Table 1. The maximum nominal particle size dmax of large-size cement-stabilized crushed stone is 63 mm. Table 1 is as follows:
[0055] Table 1 Large particle size cement stabilized crushed stone synthetic gradation table
[0056]
[0057] The large-size cement-stabilized gravel mixture is loaded into a customized detachable test mold in two layers. During the loading process, a layer of filler is first laid, and then a layer of large-size gravel is piled up. The loading and tamping are repeated until the mixture is completely loaded into the non-standard test mold. A vibration compactor is used to form a non-standard (benchmark) specimen of large-size cement-stabilized gravel. To prevent the large-size gravel from breaking during the vibration process, the exciting force of the vibration compactor is set to 6900N and the vibration frequency is set to 30Hz. The vibration is divided into two layers, and each layer vibrates for 30s to form a 200mm×200mm×200mm cubic specimen. After the non-standard (benchmark) specimen is cured for 7 days, a press is used to test the compressive strength of the large-size cement-stabilized gravel cubic specimen. The side of the formed specimen is used as the pressure surface during the test.
[0058] Furthermore, the side surface of the reference specimen is a pressure-bearing surface.
[0059] Furthermore, the three-dimensional discrete element numerical model of the specimen is constructed and the three-dimensional discrete element numerical model of the specimen is calibrated using the compressive strength value of the reference specimen to obtain the calibrated three-dimensional discrete element numerical model of the specimen, including:
[0060] Obtaining three-dimensional profile information of aggregate of the benchmark specimen;
[0061] According to the three-dimensional contour information, the large-size crushed stone is uniformly generated step by step from large to small particle sizes using the clump distribute command, and the coarse aggregate in the filling material is generated using the ball distribute command to obtain a three-dimensional discrete element numerical model of the initial specimen;
[0062] The virtual specimen was loaded, the loading speed of the left and right walls was set to 0.05 m / s, and the microscopic parameters were adjusted multiple times to obtain the calibrated three-dimensional discrete element numerical model of the specimen.
[0063] Specifically, the EinScan SPV2 desktop scanner was used to scan the large-size crushed stone aggregate to obtain the three-dimensional contour information of the large-size crushed stone aggregate; the clump distribute command was used to evenly generate large-size crushed stone in descending order of particle size; the ball distribute command was used to generate the coarse aggregate in the filler, and the fine aggregate in the filler was uniformly replaced by a ball with a radius of 2.5 mm. A numerical model of large-size cement-stabilized crushed stone with the same gradation as the benchmark specimen was constructed. The constructed model is shown in the figure. Figure 2 As shown; the contact model between the large-size crushed stone unit, the internal unit of the filler, and the large-size crushed stone and filler unit is set as a parallel bonding model, and the contact model between the wall and the aggregate is set as a linear contact model. The linear contact modulus, parallel bonding modulus, stiffness ratio, normal strength and tangential strength in the model are given initial values. The virtual sample is loaded, and the loading speed of the left and right walls is set to 0.05m / s. The stress-strain curve of the virtual sample during the loading and failure process is recorded, and the microscopic parameters are adjusted multiple times. The relative error of the calculated failure stress and Poisson's ratio of the two is 2%. The parameter calibration results are shown in Table 2. Table 2 is as follows:
[0064] Table 2 Calibration results of mesoscopic parameters of large-size cement-stabilized crushed stone
[0065]
[0066] More specifically, large-size cement-stabilized crushed stone cube virtual specimens were constructed, and the side lengths of the specimens were 2.0dmax, 2.5dmax, 3.0dmax, 3.5dmax and 4.0dmax, respectively. The compressive strength numerical simulation was performed on them, and the destructive strength values of the specimens were obtained as shown in Table 3. Table 3 is as follows:
[0067] Table 3 Average compressive strength of specimens of different sizes
[0068]
[0069] Furthermore, the ratio of the destructive strength of virtual specimens of different sizes to the destructive strength of non-standard (reference) specimens is taken as the ordinate, and the ratio of the volume of virtual specimens of different sizes to the volume of non-standard (reference) specimens is taken as the abscissa. The relationship diagram is shown below. By means of nonlinear fitting, the mathematical model of the strength ratio and volume ratio is established as follows: Figure 3 .
[0070] Specifically, the intensity volume expression is:
[0071] y=Aexp(-Bx)+C
[0072]
[0073] Where: R c For any volume V c The compressive strength value of the non-standard (benchmark) specimen (200 mm), R0 is the compressive strength value of the non-standard (benchmark) specimen (200 mm), V0 is the volume of the non-standard (benchmark) specimen, and A, B and C are fitting constants respectively.
[0074] Furthermore, the expression of the true compressive strength value is:
[0075] R' c =aR0;
[0076] Among them, R' c is the true compressive strength value of the large-size cement-stabilized crushed stone specimen, a is the compressive strength correction coefficient of the large-size cement-stabilized crushed stone non-standard specimen, and R0 is the compressive strength value of the non-standard (benchmark) specimen (200 mm).
[0077] More specifically, the established mathematical model is used to calculate that when x approaches infinity, the y value is 0.95, so the size conversion coefficient a of the compressive strength of the large-size cement-stabilized crushed stone non-standard specimen is 0.95, and the true compressive strength value R' of the large-size cement-stabilized crushed stone specimen is c It is calculated by the following formula.
[0078] R c '=0.95R0=3.47MPa.
[0079] This embodiment also provides a specimen molding device, which includes: a detachable test mold and a vibration compactor; the detachable test mold is used to load a reference specimen, and the vibration compactor is used to vibrate and compact the reference specimen.
[0080] Specifically, the detachable test mold is composed of a base 1, front and rear baffles 2, left and right baffles 3, long bolt rods 4, short bolts 5 and nuts 6. The test mold base 1 is a 280mm×280mm square with a thickness of 15mm. The front and rear baffles 2 of the test mold are a 280mm×250mm rectangle with a thickness of 10mm. The left and right baffles 3 of the test mold are a 200mm×250mm rectangle with a thickness of 10mm. The left and right baffles 3 are 30mm away from the base 1. The front and rear baffles 2 are fixedly connected by two groups of long bolt rods 4 and nuts 6, one group on each side of the left and right sides. Each group consists of two long bolt rods 4 and four nuts 6, and they are symmetrically distributed along the central axis of the test mold. The fixing spacing is 150mm. There is a protruding short bolt 5 in the middle of the base 1, which is fixed to the long bolt rod 4 by nuts 6. The schematic diagram of the structure of the large-size cement-stabilized gravel test mold is shown in Figure 4 shown.
[0081] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0082] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone, characterized in that: include: Determining a reference specimen and performing a compressive strength test on the reference specimen to obtain a compressive strength value of the reference specimen; Constructing a three-dimensional discrete element numerical model of the specimen and calibrating the three-dimensional discrete element numerical model of the specimen using the compressive strength value of the reference specimen to obtain a calibrated three-dimensional discrete element numerical model of the specimen; Using the calibrated three-dimensional discrete element numerical model of the specimen, numerical simulation of the compressive strength of large-diameter cement-stabilized crushed stone specimens of different sizes is performed to obtain a destructive strength set; According to the volumes of the large-size cement-stabilized crushed stone specimens of different sizes, the volumes of the benchmark specimens, the compressive strength values of the benchmark specimens and the destructive strength set, a strength volume expression of destructive strength and specimen size is obtained, wherein the strength volume expression includes: an abscissa expression and a strength ordinate expression; Determine the compressive strength correction factor of the large-size cement-stabilized crushed stone specimen using the strength volume expression; The true compressive strength value of the large-size cement-stabilized crushed stone specimen is obtained by using the compressive strength correction coefficient and the compressive strength value of the reference specimen.
2. The method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone according to claim 1 is characterized in that: The benchmark specimen is a large-diameter cement-stabilized gravel specimen of 200mm×200mm×200mm.
3. The method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone according to claim 1 is characterized in that: The side surface of the reference specimen is a pressure-bearing surface.
4. The method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone according to claim 1 is characterized in that: The method of constructing a three-dimensional discrete element numerical model of the specimen and calibrating the three-dimensional discrete element numerical model of the specimen using the compressive strength value of the reference specimen to obtain a calibrated three-dimensional discrete element numerical model of the specimen includes: Obtaining three-dimensional profile information of aggregate of the benchmark specimen; According to the three-dimensional contour information, the large-size crushed stone is uniformly generated step by step from large to small particle sizes using the clump distribute command, and the coarse aggregate in the filling material is generated using the ball distribute command to obtain a three-dimensional discrete element numerical model of the initial specimen; The virtual specimen was loaded, the loading speed of the left and right walls was set to 0.05 m / s, and the microscopic parameters were adjusted multiple times to obtain the calibrated three-dimensional discrete element numerical model of the specimen.
5. The method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone according to claim 1 is characterized in that: The intensity volume expression is: y=Aexp(-Bx)+C Where: R c For any volume V c The compressive strength value of the non-standard specimen, R0 is the compressive strength value of the non-standard specimen, V0 is the volume of the non-standard specimen, exp is the exponential fitting formula, and A, B and C are the fitting constants respectively.
6. The method for correcting the compressive strength of non-standard specimens of large-size cement-stabilized crushed stone according to claim 1, characterized in that: The expression of the true compressive strength value is: R' c =aR0; Among them, R' c is the true compressive strength value of the large-size cement-stabilized crushed stone specimen, a is the compressive strength correction coefficient of the non-standard specimen of large-size cement-stabilized crushed stone, and R0 is the compressive strength value of the non-standard specimen.
7. A specimen forming device, applied to the method according to any one of claims 1 to 6, characterized in that: The test piece forming equipment comprises: Removable test mold and vibratory compactor; The detachable test mold is used to load the reference test piece, and the vibration compactor is used to perform vibration compaction on the reference test piece.
8. A test piece forming device according to claim 1, characterized in that: The detachable trial mold comprises: Base, front and rear baffles, left and right baffles, long bolt rods, short bolts and nuts; The front and rear baffles and the left and right baffles are installed at the front, rear, left and right positions of the base. The front and rear baffles are fixedly connected by two groups of long bolt rods and nuts, one group on each side. Each group consists of two long bolt rods and four nuts, and are symmetrically distributed along the central axis of the test mold. There is a protruding short bolt in the middle of the base and it is fixed to the long bolt rod by a nut.
Citation Information
Patent Citations
Graded broken stone anisotropic parameter determination method based on virtual triaxial test
CN113553750A
Modeling method for asphalt mixture by coupling discrete element method and finite difference method
US20210090326A1